Uganda’s Tax Policy: Identifying and addressing the gaps - Tibemanya Rwemisisi, Jude (Africa Leadership Institute, 2018)
This policy brief is based on two research studies conducted by scholars of Taxation and Public Administration based at Makerere University Kampala (MaK) and Uganda Management Institute (UMI) respectively. The research studies titled Public Aversion to Tax in Uganda: Political and Public Administration Perspectives and Improving Tax Revenue in Uganda were commissioned by Uganda Policy Development Management Forum (UPDMF) with support from UMI and Africa Leadership Institute (AFLI). The studies were conducted in response to an expressed public need to streamline the process of introduction, collection and accountability for taxes.